Estudo de íons cobre no mecanismo de formação de complexo com resveratrol em modelo de células MCF-7 - Volkart, Priscylla Andrade (2017)
The redox-active chemical properties of trace element copper make it an essential cofactor for several cellular mechanisms, as for ROS production. Polyphenols have been used in the pro-oxidant mechanism of action of interaction with endogenous Cu (II) ions for the production of reactive oxygen species in excess as a treatment for malignancies, leading to apoptosis. This work studied Cu (II) ions in the complex formation mechanism with Resveratrol in MCF-7 cells model. We analyzed the selectivity of Resveratrol in relation to the cupric metal ion using HPLC (High-Performance Liquid Chromatography) and the formation of the compound Resveratrol-Copper through UV-VIS (Ultra-Violet Visible Spectrophotometry). We analyzed the cellular morphology and location of the metal ion by MET-EDS (Electronic Transmission microscopy with Dispersive X-ray Spectroscopy). Cell death by apoptosis and quantification of ROS in said cell line with copper enrichment and treated with Resveratrol was made by flow cytometry. The results show the selectivity of the polyphenol compound by copper ion as well as the formation of the complex Resveratrol-Copper in extracellular conditions, however even with verification of endogenous copper accumulation in physiological conditions in vitro, the formation of that complex did not occur because there was no production of ROS and therefore, no cell death. In short, our research reveals that for in vitro conditions for the MCF-7 line, there's no Resveratrol-Copper complex formation as observed in sub-lethal quantities of chemically enriched cells with CuSO4 and treated with Resveratrol.